Molecular analysis of strawberry cultivars using RAPD, AP-PCR and STS markers - A. Balogh; E. Kiss; A. Szőke; F. Dénes; L. Heszky (International Journal of Horticultural Science, 2002)
Seventeen strawberry (Fragaria x ananassa Duch.) cultivars representing the national list of Hungary, were subjected to RAPD, AP—PCR and STS analysis. Of the 31 decamer and oligomer primers tested 26 primers produced polymorphic patterns. 45 polymorphic fragments were analysed, ranging between 200-2800 by in size. Based on the data, similarity coefficients (Jaccard index and Simple matching coefficient) were calculated, and dendrograms were constructed using the unweighted pair group method of arithmetic averages (UPGMA). The dendrograms only partly reflect the known pedigree data. Specific RAPD markers were identified for cultivars F5, Pocahontas and Rabunda.